2007
DOI: 10.1182/blood-2007-01-071167
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-cleaved HPK1 induces CD95L-independent activation-induced cell death in T and B lymphocytes

Abstract: Life and death of peripheral lymphocytes is strictly controlled to maintain physiologic levels of T and B cells. Activation-induced cell death (AICD) is one mechanism to delete superfluous lymphocytes by restimulation of their immunoreceptors and it depends partially on the CD95/CD95L system. Recently, we have shown that hematopoietic progenitor kinase 1 (HPK1) determines T-cell fate. While full-length HPK1 is essential for NF-κB activation in T cells, the C-terminal fragment of HPK1, HPK1-C, suppresses NF-κB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 57 publications
(73 reference statements)
1
35
0
1
Order By: Relevance
“…[6][7][8][9] The adhesion and degranulation promoting adaptor protein (ADAP) forms a complex with Src kinase-associated phosphoprotein 55 kD (SKAP55) and Ras-associated protein 1 (Rap1)-GTP-interacting adaptor molecule (RIAM). ADAP binds to SLP-76 in a TCR-stimulation dependent manner to translocate the ADAP-SKAP55-RIAM complex to the cell membrane and further recruit the active small GTPase Rap1.…”
Section: Gck-i Kinases Regulate Nf-kb Activation Integrin Activity mentioning
confidence: 99%
“…[6][7][8][9] The adhesion and degranulation promoting adaptor protein (ADAP) forms a complex with Src kinase-associated phosphoprotein 55 kD (SKAP55) and Ras-associated protein 1 (Rap1)-GTP-interacting adaptor molecule (RIAM). ADAP binds to SLP-76 in a TCR-stimulation dependent manner to translocate the ADAP-SKAP55-RIAM complex to the cell membrane and further recruit the active small GTPase Rap1.…”
Section: Gck-i Kinases Regulate Nf-kb Activation Integrin Activity mentioning
confidence: 99%
“…The best studied is the extrinsic, cell death receptor-dependent pathway, 2 although death receptor-independent pathways also exist. 3,4 Activated natural killer (NK) cells are also eliminated via death receptor signalling. However, in some NK cells restimulation of activating receptors such as CD94, 5 CD2 6 or CD16 5,7,8 results in very rapid death, independent of death receptor signalling.…”
mentioning
confidence: 99%
“…The involvement of FasL-Fas-mediated killing has also been evident in CSup-induced cell death. Experiments using long-term (at least 18-h) cell cultures have shown that AICD of T cells may occur in both a Fas-dependent (1-3) and Fas-independent manner (4)(5)(6)(7)(8)50).…”
Section: Discussionmentioning
confidence: 99%